THE CORRELATION BETWEEN THE HISTORY OF EXCLUSIVE BREASTFEEDING, MACRONUTRIENT INTAKE, AND ZINC INTAKE IN CHILDREN AGE 6-59 MONTH AT KEJAJAR 2 HEALTH CENTER WONOSOBO - Noviasari; Desy Putriningtyas, Natalia (JURNAL KESMAS DAN GIZI (JKG), 2023)
Stunting is a global health problem that needs attention. Wonosobo Regency has one of the highest stunting rates in Central Java at 15.97% and Kejajar 2 Health Centre has the 4th highest stunting prevalence in Wonosobo at 23.88% in February 2023. The causes of stunting are maternal factors, breastfeeding, inadequate supplementary food, and a history of chronic infectious diseases. This study aims to determine the relationship between exclusive breastfeeding, macronutrient intake, and zinc intake in children 6-59 months at Puskesmas Kejajar 2. This study uses a type of quantitative research with an analytical observational design and a case control approach. The research instruments used were KMS (Kartu Menuju Sehat), SQ-FFQ (Semi Quantitative-Food Frequency Quesionare) questionnaire, and microtoise or infantometer. The sampling technique was quota sampling with a total of 172 respondents, with a ratio of case and control groups 1: 1. The data analysis performed was univariate analysis and bivariate analysis with the Chi Square test. The results showed that exclusive breastfeeding did not show a significant relationship with the incidence of stunting with a p-value of 0.321 or p>0.05 and there was a relationship between protein, fat, carbohydrate, and zinc intake with the incidence of stunting with a p-value of 0.000 or p<0.05. So it can be concluded that exclusive breastfeeding has no significant relationship with the incidence of stunting, while macronutrient intake and zinc have a significant relationship with the incidence of stunting at Puskesmas Kejajar 2 Wonosobo.